2016
DOI: 10.1038/srep18829
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and DFT investigation of new bismuth-containing MAX phases

Abstract: The Mn + 1AXn phases (M = early transition metal; A = group A element and X = C and N) are materials exhibiting many important metallic and ceramic properties. In the present study powder processing experiments and density functional theory calculations are employed in parallel to examine formation of Zr2(Al1−xBix)C (0 ≤ x ≤ 1). Here we show that Zr2(Al1−xBix)C, and particularly with x ≈ 0.58, can be formed from powders even though the end members Zr2BiC and Zr2AlC seemingly cannot. This represents a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(94 citation statements)
references
References 43 publications
6
88
0
Order By: Relevance
“…Gao et al [20] recently investigated solid solutions in the Ti 3 (Al 1−x Si x )C 2 system and found not only stable solid solutions through the entire composition range but also significant solid-solution hardening without compromising oxidation resistance. Finally, Horlait et al [16] provided the first evidence for Bi-containing MAX phases (Zr 2 Al 1−x Bi x C with x ∼ 0.58), while Lapauw recently reported the synthesis of Zr 2 AlC, albeit in a two-phase microstructure with ZrC being the secondary phase [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al [20] recently investigated solid solutions in the Ti 3 (Al 1−x Si x )C 2 system and found not only stable solid solutions through the entire composition range but also significant solid-solution hardening without compromising oxidation resistance. Finally, Horlait et al [16] provided the first evidence for Bi-containing MAX phases (Zr 2 Al 1−x Bi x C with x ∼ 0.58), while Lapauw recently reported the synthesis of Zr 2 AlC, albeit in a two-phase microstructure with ZrC being the secondary phase [21].…”
Section: Introductionmentioning
confidence: 99%
“…Mixing in the A sublattice has been recently investigated experimentally and computationally [16]. Bei et al [17], for example, investigated Ti 2 Al 1−x Sn x C solid solutions and concluded that the addition of low melting elements in the A sublattice of aluminum-containing MAX phases could lead to reduction of oxidationinduced crack healing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…the energy barriers for diffusion) [16][17][18][19]. Controlling point defects such as vacancies is important for semiconductors, superconductors, and oxides [20][21][22][23][24][25][26][27][28]. A way to defect engineer the concentration and clustering of point defects in the anion sublattice (for example oxygen vacancies) is via the introduction of dopants.…”
mentioning
confidence: 99%
“…In the past few decades of the miniaturization of devices, the introduction of more structurally complicated materials in conjunction with demanding processing and operating conditions have made the study of defects in materials increasingly important [1][2][3][4][5][6][7][8][9][10]. There is no single recipe of how to treat materials and what is the optimum concentration of defects.…”
Section: Introductionmentioning
confidence: 99%